„Chyba tylko zapisać wrażenia z lektury, choć ja mam manię sprawdzania realiów”. Z profesor Krystyną Poklewską rozmawiają Krystyna Pietrych i Tomasz Cieślak - Poklewska, Krystyna; Pietrych, Krystyna; Cieślak, Tomasz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
In an interview with Krystyna Pietrych and Tomasz Cieślak, Krystyna Poklewska,professor emerita of the Łódź University, discusses the first years of the Faculty ofPhilology and Polish Studies in Łódź. It was also when she started her studies afterleaving the destroyed Warsaw. She mentions numerous great individuals who usedto work there, such as Jan Dürr-Durski, Samuel Sandler, Stefan Kawyn or ZdzisławSkwarczyński. The Professor considers her own career as a scholar: her earliest yearsmarked by the strong influence of Kawyn, until the most recent time, which foundher with inexhaustible passion for working with the literature of Polish Romanticism.